PERINATAL OUTCOME OF NUCHAL CORD - Zahoor, Farnaz; Minhas, Zakia; Zaki, Adil (Journal of Postgraduate Medical Institute, 2013)
Objective: To find out the perinatal outcome in cases of vaginal delivery with nuchal cord versus babies delivered by elective ceaserian section with nuchal cord. Methodology: A retrospective, cross-sectional, comparative study done between January to December 2011at Kalsoom Maternity Hospital where 1776 patients were analyzed for presence of nuchal cord prior toand at the time of delivery and perinatal outcome. The cases with nuchal cord undergoing vaginal deliverywere 205 (study group) versus 85 elective ceaserian section with nuchal cord served as control group.Outcome variables between the two groups were compared. Results: Incidence of nuchal cord was 16.3%. Incidence of single nuchal cord was highest in normaldelivery (73.9%). No significant difference was found between the mean of both 1- and 5-minute Apgarscores (8 and 10, respectively) between the two groups, but infants born with nuchal cords vaginally,tended to have lower scores at 1 minute (p=0.008). This trend was not evident in the 5-minute Apgar test.Two neonatal admission were done (in vaginal delivery group) for 24 hour and then discharged for babies with apgar score 3/10, 5/10 and 4/10, 6/10 respectively. Elective ceaserian section cause an additionalmorbidity and does not justify in case of nuchal cord as outcome is almost same in both condition. Conclusion: Nuchal cord is not associated with adverse perinatal outcome therefore do not influenceclinical management. Doing elective section is not justified as there is no difference in perinatal outcome.